Energy Transduction in Biological Membranes : A Textbook of Bioenergetics - Cramer, William A.; Knaff, David B.; SpringerLink (Online service) (1991)
Energy Transduction in Biological Membranes was primarily designed for graduate courses in bioenergetics. Not only does it discuss basic principles and concepts central to modern membrane biochemistry, biophysics and molecular biology, but also (1) the components and pathways for electron transport and hydrogen ion translocation, and (2) the utilization of electrochemical ion gradients. The book is unique in presenting a comparative treatment of respiratory and photosynthetic energy transduction, and in using protein sequence data coupled with physical concepts to discuss the mechanisms of energy transducing proteins.
Keywords: Chemistry; Chemistry, Physical organic; Biochemistry; Electronic books